2022
DOI: 10.3390/su14158983
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Tourism: A Literature Review to Assess Implications, Multiple Impacts, Vulnerabilities, and Future Perspectives

Abstract: Cycle tourists are increasingly prominent in the profile of world tourism and, in the light of the literature, it is essential, among other things, to examine more closely who they are, what their concerns and motivations are that generate the choice of a cycle tourism product, and, as a priority, the level of economic, social, and environmental impact they cause at destination. In this context, this literature review aims at identifying authors’ and publishers’ interest in cycle tourism, the positive and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The improvement of cycle tourism services can bring benefits both for inhabitants and for tourists, in a sustainable development perspective. For the inhabitants, cycling tourism can determine the enhancement of territorial capital (natural, cultural, and human), the creation of new opportunities for investment and new jobs in different related sectors, and the growth of the local economy, but also, the radical shifts to more sustainable mobility habits in commuting from home to work, or even for recreational purposes in relation to proximity tourism [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improvement of cycle tourism services can bring benefits both for inhabitants and for tourists, in a sustainable development perspective. For the inhabitants, cycling tourism can determine the enhancement of territorial capital (natural, cultural, and human), the creation of new opportunities for investment and new jobs in different related sectors, and the growth of the local economy, but also, the radical shifts to more sustainable mobility habits in commuting from home to work, or even for recreational purposes in relation to proximity tourism [14].…”
Section: Discussionmentioning
confidence: 99%
“…The research debate on cycle tourism, as stated in a recent literary review, outlines a trend of development of this economic sector in general, and it also suggests that a finer filter of attention should be applied to those touristic experiences that can be defined by more specific adjectives such as slow, green, sustainable, proximity and cultural [14]. Also considering the framework of UN SDGs (n.3, 9 and 11) [58], the research has shown a method to support the definition of new strategies in the field of sustainable tourism, to reduce greenhouse gas emissions and define new environmentally friendly travel patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bibliometric method used in this research has also been used in many special subjects in the field of tourism before. Some of the studies prepared by the bibliometric method are as follows: length of stay (Atsiz et al 2022), cycling tourism (Ciascai et al 2022), diaspora tourism (Çiki 2022), wine tourism (Durán-Sánchez et al 2016), tourism journals (Hall 2006;Mulet-Forteza et al 2018;Merigó et al 2019), sports tourism (Jiménez-García et al 2020), smart tourism (Johnson, Samakovlis 2019), tourism studies (Nińerola et al 2019), slow tourism (Oh et al 2016), dark tourism (Ogretmenoglu et al 2022), food and gastronomy research (Okumus et al 2018), etc. The authors used the Web of Science database to generate a dataset on research on film tourism.…”
Section: Methodsmentioning
confidence: 99%
“…This effort will be aided by continued investment in bicycle infrastructure in both small towns and cities. This will ensure that cyclists are safe whenever they are on the road or cycling between cities [15][16][17][18]. Pollutants are found in the atmosphere, such as gases and dust.…”
Section: Introductionmentioning
confidence: 99%